PYROELECTRIC ORGANO-RUTHENIUM LANGMUIR-BLODGETT SUPERLATTICES - Colbrook, R; Richardson, T; Poulter, M; Roberts, G; Polywka, M; Davies, S (1990)
The Langmuir-Blodgett film-forming properties of an organo-ruthenium complex (cyclopentadienyl (bis triphenylphosphine) ruthenium (4-heptadecycloxybenzonitrile) hexafluorophosphate) are reported. Different types of non-centrosymmetric films of this compound suitable for pyroelectric thermal imaging are compared. Alternate layer superlattices, in which the ruthenium complex is alternated with a long chain fatty acid (behenic acid), are found to possess superior structural stability and exhibit a larger pyroelectric activity. Their pyroelectric and dielectric properties are described and the figure of merit of such superlattices deployed in thermal imaging devices is discussed. © 1990.